The Agribusiness Ecosystem in East and Southern Africa: Exploring the Role and Synergies of Key Stakeholders in the Space - With, Lisa; Inoubli, Aziza; Onkware Sarangé, Clara; Adebola, Mariam (CGIAR System Organization, 2022)
Despite the potential of the agriculture sector in Africa to meet global food demands, performance across key areas has remained low. Farmers and market systems continue to be inhibited by fragmentation, poor efficiency of value chains, and limited resilience against climate shocks. The ones that suffer the most from these inefficiencies and threats are smallholder farmers. The potential impact of targeting these market gaps is immense. Agribusinesses and agritechs across East and Southern Africa (ESA) are at the forefront of transforming the sector, offering new innovations that increase yields and productivity sustainably, de-risk and improve value chain linkages, increase farmer incomes, and strengthen land, food, and water systems. To support the growth of private sector solutions, significant investments and support is needed. Ukama Ustawi meaning “well-being” is a project aimed at supporting climate-resilient agriculture and livelihoods in 12 countries in East and Southern Africa by helping millions of smallholder farmers intensify, diversify, and de-risk maize-mixed farming through: a) supporting sustainable crop management and diversification, b) empowering women, youth, marginalised individuals, agripreneurs, and other agri stakeholders, c) promoting healthy diets and nutrition, and d) protecting the environment from degradation and unsustainable land use and practices. Against this backdrop, ‘The Agribusiness Ecosystem in East and Southern Africa’ is a report that provides a market assessment of nine countries across the ESA region and across four key stakeholder groups to inform the development of a science-driven accelerator programme for climate-smart agribusinesses, and identify the relations and technical assistance needs of agribusinesses, funding partners, entrepreneur support organisations, and agriculture corporates. The study has been developed leveraging data from the Briter Intelligence platform, desk research, and interviews with key stakeholders across the space. The agribusiness ecosystem is ripe for innovation, and one of the first steps to creating impactful change is understanding and targeting alignment between the challenges and needs of key players.